(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
In today’s time, when there are so many trials, one should be prepared for them. This is also the reason why many people, especially young people and students, give up even though they have never tried to do it. Because of the lack of self-confidence and not being prepared for the courses or paths to be taken, everything usually goes to nothing. Based on the results and interpretations of data in the study, some students can overcome the trials that come in their lives as much as they can, and others will find other ways to overcome all of the trials. Based on the results presented, the following recommendations are forwarded: students should make sure they enjoy studying, computing, and presenting with numbers because it has a significant impact on how well-prepared they are for the Accountancy program. As a student, it is appropriate to develop these skills further by taking the accountancy program course so that it is easy to overcome every challenge that comes up in life. Students should practice more analytical skills by playing Sudoku, puzzles, chess, or crosswords so that their minds develop even deeper decision-making that can be used in real life. Students who intend to enroll in the Accountancy program in the upcoming academic year must first learn the accounting subject in order to ensure that they are sufficiently prepared to study accounting.